2018
DOI: 10.1097/mat.0000000000000654
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Rat Lung Scaffolds Using Sodium Lauryl Ether Sulfate for Tissue Engineering

Abstract: Perfusion decellularization with detergents is effective to maintain the architecture and proteins of extracellular matrix (ECM) for use in the field of lung tissue engineering (LTE). However, it is unclear which detergent is ideal to produce an acellular lung scaffold. In this study, we obtained two decellularized rat lung scaffolds using a novel detergent sodium lauryl ether sulfate (SLES) and a conventional detergent sodium dodecyl sulfate (SDS). Both decellularized lung scaffolds were assessed by histology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 37 publications
11
28
0
1
Order By: Relevance
“…Recently, a comparative study about heart decellularization using SLES and SDS in rats demonstrated that GAGs concentration and collagen contents were preserved in SLES‐treated hearts more than SDS. Moreover, better scaffold preservation of the rat kidney and lung was reported by SLES in comparison with SDS (Kawasaki et al, ; Ma et al, ). Some previous studies reported a reduction in the GAG contents of the Triton X‐100/ SDS‐treated liver, articular cartilage, and heart (Bruyneel & Carr, ; Wu et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, a comparative study about heart decellularization using SLES and SDS in rats demonstrated that GAGs concentration and collagen contents were preserved in SLES‐treated hearts more than SDS. Moreover, better scaffold preservation of the rat kidney and lung was reported by SLES in comparison with SDS (Kawasaki et al, ; Ma et al, ). Some previous studies reported a reduction in the GAG contents of the Triton X‐100/ SDS‐treated liver, articular cartilage, and heart (Bruyneel & Carr, ; Wu et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…SDS, with a hydrophobic chain and a charged headgroup, as a strong and harsh detergent lyses cell membrane and solves the structural proteins by interruption of noncovalent bonds between proteins, while Triton X‐100 with uncharged headgroup and hydrophilic chain is not as effective as SDS, but it preserves ECM molecules in the decellularized tissue more intact (Li et al, ). Sodium lauryl ether sulfate (SLES), an anionic and novel detergent in field of decellularization, is newly proposed in literature (Hassanpour, Talaei‐Khozani, Kargar‐Abarghouei, Razban, & Vojdani, ; Kawasaki et al, ; Ma et al, ) and selected in this study for rat liver decellularization.…”
Section: Introductionmentioning
confidence: 99%
“…Although SDS is routinely used in many decellularization protocols [ 32 ], a long-term treatment significantly alters the ECM, has a strong damaging effect on the ultrastructure of the native tissue, including reduction of the glycans and cytokines, is cytotoxic, has poor attachment property, and induces inflammation and thrombus formation after transplantation [ 32 34 ]. Previously, studies showed that SLES, a milder anionic detergent, could decrease the drawbacks related to SDS and may be a more suitable reagent for decellularization [ 35 , 36 ]. Since the ovary does not have an extensive vasculature, immersion and agitation is an approach for decellularization, and depends on the size and thickness of the samples, immersion duration and the intensity of agitation will be different [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SLES showed better preservation of proteoglycans, cytokines (such as basic FGF) and ECM microstructures, including ECM laminar array and basement membranes around the vasculature, than SDS. These results indicated that SLES-treated decellularized scaffolds could be superior to those treated with SDS as the niche for stem cell differentiation [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel anionic detergent, sodium lauryl ether sulfate (SLES) with mild properties, excellent detergency and dispersion performance, has been reported with the improved decellularization effect of the rat heart and lung (Ćirin, Poša, & Krstonošić, 2011;Kawasaki et al, 2015;Ma et al, 2018). And we hypothesized that it may be suitable for human cancer tissues.…”
mentioning
confidence: 99%